APLIKASI KLINIK UMKM UNTUK MENDUKUNG FOOD COMMUNITY UMKM BANDUNG - Anak Agung Gde Agung; Rennyta Yusiana; Rizza Indah Mega Mandasari; Kristina Sisilia; Heru Nugroho; Taufan Umbara; Astadi Pangarso; Agus Maolana Hidayat; Dewi K. Soedarsono (LPPM Universitas Bina Bangsa, 2023)
As the spearhead of the economy, Micro, Small and Medium Enterprises (MSMEs) play a very important role in Indonesia. MSMEs employ more than 99% of the workforce and contribute greatly to our country's gross domestic product. The Covid-19 pandemic that occurred at the end of 2020 caused drastic changes in daily habits, including interactions and transactions. For health reasons, people are forced to use IT in interacting and transacting. This is actually in line with the government's plan to utilize IT for economic activities, but the pandemic has accelerated this so that MSMEs must be able to adapt in a very short time. Food Community (Footy) is an MSME community focused on the food sector operating in the Bandung area. Currently, the community requires an IT-based platform to communicate with their SMEs member. This communication includes MSME consulting from legality arrangements to branding, design and marketing, institutional consulting, and management of activities such as workshops and seminars. For this reason, in this community service activity, we proposed an IT-based platform in the form of an MSME clinic website that can be used by MSME members and other parties involved in community operations, such as academic and government institutions. In this activity, we also provide supporting equipment for MSME clinical activities